2016
DOI: 10.1016/j.envres.2016.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Non-thyroid cancer incidence in Belarusian residents exposed to Chernobyl fallout in childhood and adolescence: Standardized Incidence Ratio analysis, 1997–2011

Abstract: Background While an increased risk of thyroid cancer from post-Chernobyl exposure to Iodine-131 (I-131) in children and adolescents has been well-documented, risks of other cancers or leukemia as a result of residence in radioactively contaminated areas remain uncertain. Methods We studied non-thyroid cancer incidence in a cohort of about 12,000 individuals from Belarus exposed under age of 18 years to Chernobyl fallout (median age at the time of Chernobyl accident of 7.9 years). During 15 years of follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…(2931)], and a case-control study which showed a significant association of leukemia risk with increasing radiation dose in Ukraine (but not in Belarus or Russia) could be due to sampling-derived bias (32). In the UkrAm and BelAm cohorts of children there have only been 11 cases of leukemia, suggesting a small but nonsignificant increase in risk (33, 34).…”
Section: Late Cancer-related Health Effects In the General Populationmentioning
confidence: 98%
“…(2931)], and a case-control study which showed a significant association of leukemia risk with increasing radiation dose in Ukraine (but not in Belarus or Russia) could be due to sampling-derived bias (32). In the UkrAm and BelAm cohorts of children there have only been 11 cases of leukemia, suggesting a small but nonsignificant increase in risk (33, 34).…”
Section: Late Cancer-related Health Effects In the General Populationmentioning
confidence: 98%
“…Nevertheless, there have been many post-Chernobyl studies of leukaemia and cancer morbidity in the populations of 'contaminated' areas in the three countries. In relation to the increase in the incidence of leukemia after irradiation in utero or during childhood, about ten ecological studies were carried out in three countries from 1993 to 2003, and the effect -2016, for example, [24][25][26] the results are contradictory. The same conclusion regarding non-thyroid cancer and breast cancer alone was made in.…”
Section: Leukaemia and Solid Cancer Other Than Thyroid Cancermentioning
confidence: 99%
“…The same conclusion regarding non-thyroid cancer and breast cancer alone was made in. 25,26) It is thought, however, that for most solid cancers, the minimum latent period is of the order of 10 radiological impact of the accident.…”
Section: Leukaemia and Solid Cancer Other Than Thyroid Cancermentioning
confidence: 99%